2015
DOI: 10.1021/acs.est.5b01031
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Clinically Relevant Antibiotic-Resistance Genes, Bacterial Load, and Metals in Freshwater Lake Sediments in Central Europe

Abstract: Wastewater treatment plants (WWTP) receive the effluents from various sources (communities, industrial, and hospital effluents) and are recognized as reservoir for antibiotic-resistance genes (ARGs) that are associated with clinical pathogens. The aquatic environment is considered a hot-spot for horizontal gene transfer, and lake sediments offer the opportunity for reconstructing the pollution history and evaluating the impacts. In this context, variation with depth and time of the total bacterial load, the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
92
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(104 citation statements)
references
References 40 publications
6
92
0
Order By: Relevance
“…Some recent studies performed in the similar environment demonstrated that the various attributes of watersheds, such as morphological and geological factors, as well as the local socioeconomic conditions, lack of adequate sanitation and uncontrolled landfills can influence the status of surface and ground water bodies through physical, chemical, biological or bacteriological parameters (e.g. Tshibanda et al 2014;Devarajan et al 2015a;Tallar and Suen 2015). The presence of high concentration of soluble ions such NO 3 - Table 3 Average concentration of soluble ions of water samples from selected wells during the dry season (dry) and wet season (wet) (Banks et al 2002).…”
Section: Results and Discussion Physicochemical Quality Of Watermentioning
confidence: 99%
“…Some recent studies performed in the similar environment demonstrated that the various attributes of watersheds, such as morphological and geological factors, as well as the local socioeconomic conditions, lack of adequate sanitation and uncontrolled landfills can influence the status of surface and ground water bodies through physical, chemical, biological or bacteriological parameters (e.g. Tshibanda et al 2014;Devarajan et al 2015a;Tallar and Suen 2015). The presence of high concentration of soluble ions such NO 3 - Table 3 Average concentration of soluble ions of water samples from selected wells during the dry season (dry) and wet season (wet) (Banks et al 2002).…”
Section: Results and Discussion Physicochemical Quality Of Watermentioning
confidence: 99%
“…Previously, culturable and molecular measurements of ENT and EC were enumerated from 60 cm beneath the surface sediment in Lake Geneva, Switzerland. 9,36 Both studies further suggest that sediments are long-term reservoirs for FIB that originate in gastrointestinal tracts of humans and or mammals. Attachment of cells to solid particles like sediment may protect the cell wall from degradation with unknown mechanisms.…”
Section: ■ Discussionmentioning
confidence: 93%
“…The aquatic environment is considered a hot-spot for horizontal gene transfer, and lake sediments offer the opportunity for reconstructing the pollution history and evaluating the impacts. The contamination of sediments by untreated or partially treated effluent water can affect the quality of ecosystem [26]. As the gram negative bacteria have a reservoir in the intestines of man and other warm blooded animals, are excreted in feces and are known to survive in the environment but do not reproduce [27].…”
Section: Discussionmentioning
confidence: 99%